Length of Hospitalization and Clinical Outcomes for Pneumonia Patients at PKU Muhammadiyah Hospital, Bantul - Umam Kurniawan, Nurcholid; Sukirto, Novi Wijayanti; Prisilla, Elvina; Rahayu, Ana Budi; Yuniasih, Dewi; Ari Mulyani, Dewi; Ulfa, MH Muflihatul (Ahmad Dahlan Medical Journal, 2024)
Pneumonia is a lower respiratory tract infection that was the leading cause of death in developing countries in 2020, it was shown that pneumonia was the largest contributor to post-neonatal (14.5%) and under-five deaths (5.05%). The timing of hospital discharge for patients with pneumonia is determined primarily by the attending physician and is based on an assessment of the patient's clinical stability and the appropriate duration of inpatient medical therapy. The patient's discharge decision determines the length of hospital stay. Objective: To determine the length of hospitalization and clinical outcome improvement of pneumonia patients at PKU Muhammadiyah Bantul Hospital. Methods: This study was a cross-sectional descriptive study using a retrospective study conducted by taking medical record data at PKU Muhammadiyah Bantul Hospital Results: Pneumonia patients at PKU Muhammadiyah Bantul Hospital were dominated by the age group of 2 years old while by gender the majority were boys. Length of Stay (LOS) of pneumonia patients was highest with three days of treatment as many as 136 patients or 54.2%. Conclusion: Cumulatively within seven days, 98.80% of pneumonia patients showed good clinical outcomes and were allowed to leave the hospital. it is not known for certain that patient outcomes are related to the patient's length of stay because all patients returned home in improved condition after treatment at the hospital.